KEBEBASAN BEREKSPRESI DAN UJARAN KEBENCIAN DI MEDIA SOSIAL - Oktafiani Herlina (AKADEMI KOMUNIKASI RADYA BINATAMA, 2022)
Hate speech is a phenomenon that often occurs on social media. Social media is thehighest channel for spreading hate speech because of the freedom of expression. Hatespeech can occur due to political, economic, religious differnces, and social and culturalinequalities. The purpose of this research is to find out how freedom of expression can beused as a pretext for hate speech. This study uses a qualitative approach because it canexplain reality by using descriptive explanations. In addition, it will also be easier toa djust tothe henomena occur. The result is that social media users are not afraid to make speecheson social media because communication on social media is horizontal, users do not dealdirectly with other users, and can create fake personal identities causing users to feelsafedoing anything on social media.